SIMULASI PENGUJIAN PRESTASI SUDU TURBIN ANGIN - Sulistyo Atmadi; Ahmad Jamaludin Fitroh (Jurnal Teknologi Dirgantara, 2006)
Identification of whether aerodynamic performances of a rotor blades has met the criteria according to its design or not, the general procedure is to fabricate and perform a field testing; or testing its model in a windtunnel. Both method require high cost however; therefore, a simulation method using Fluent software had used for obtaining lower cost. The model used in an LS (1)-0417 Mod airfoil having 3 blades and rotor diameter 7.21 m. Simulation test shows a good result with a difference of 4.61 percent for torque and power from design result. Keywords: Sud, Turbin angin, Fluent.